Pirfenidone reduces ovarian fibrosis and improves PCOS in letrozole-induced rat model - Ayşe Çakır Gündoğdu; Neziha Senem Arı; Ahmet Koçak; Gülnihal Şenol; Asiye Höbel; Ömer Eldiven; Fatih Kar; Orhan Özatik (Biomolecules & Biomedicine)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder characterized by cystic ovarian morphology, anovulation, and infertility. Ovarian fibrosis has recently emerged as a key pathological feature of PCOS. This study investigated whether pirfenidone (PFD), an antifibrotic agent, could improve ovarian dysfunction in a letrozole-induced PCOS rat model. Forty-two female Wistar albino rats were divided into six groups (n=7 each): control, PFD, PCOS, PCOS/PFD, PCOS/combined oral contraceptives (COC), and PCOS/PFD/COC. PCOS was induced using letrozole (1 mg/kg/day orally for 21 days). PFD (200 mg/kg/day) and/or COC (0.18 mg/kg cyproterone acetate and 0.00315 mg/kg ethinyl estradiol) were administered for 21 days. Compared to controls, PCOS rats exhibited significant disruptions in estrous cyclicity, ovarian morphology, and fibrosis-related markers (all p<0.0001), despite no significant changes in testosterone (p=0.058) or estrogen (p=0.896) levels. PFD treatment significantly improved estrous cyclicity, follicular profile, and corpora lutea count (all p<0.0001), reduced ovarian fibrosis (p<0.0001), downregulated TGF-β1, CTGF, and MMP-9 (all p<0.0001), and upregulated PPAR-γ and MMP-2 (both p<0.0001), without affecting hormone levels (p=0.945 and p=0.479, respectively). COC treatment also improved estrous cyclicity and ovarian histology (all p<0.0001), reduced fibrosis (p=0.005), and modulated TGF-β1, CTGF, MMP-9, and PPAR-γ expression (p=0.0001 to <0.0001), but had no effect on MMP-2 (p=0.868). Combination therapy (PCOS/PFD/COC) provided additional improvement in corpora lutea count (p<0.0001 vs. PCOS/PFD) and collagen deposition (p=0.002 vs. PCOS/PFD) but did not confer further benefits in fibrosis-related marker expression or folliculogenesis (all p>0.05). These findings suggest that pirfenidone mitigates PCOS pathology by targeting ovarian fibrosis, supporting antifibrotic therapy as a novel and promising approach.